3D aggregate culture improves metabolic maturation of human pluripotent stem cell derived cardiomyocytes. Issue 3 (11th December 2017) - Correia, Cláudia; Koshkin, Alexey; Duarte, Patrícia; Hu, Dongjian; Carido, Madalena; Sebastião, Maria J.; Gomes‐Alves, Patrícia; Elliott, David A.; Domian, Ibrahim J.; Teixeira, Ana P.; Alves, Paula M.; Serra, Margarida
Abstract: Three‐dimensional (3D) cultures of human pluripotent stem cell derived cardiomyocytes (hPSC‐CMs) hold great promise for drug discovery, providing a better approximation to the in vivo physiology over standard two‐dimensional (2D) monolayer cultures. However, the transition of CM differentiation protocols from 2D to 3D cultures is not straightforward. In this work, we relied on the aggregation of hPSC‐derived cardiac progenitors and their culture under agitated conditions to generate highly pure cardiomyocyte aggregates. Whole‐transcriptome analysis and 13 C‐metabolic flux analysis allowed to demonstrate at both molecular and fluxome levels that such 3D culture environment enhances metabolic maturation of hiPSC‐CMs. When compared to 2D, 3D cultures of hiPSC‐CMs displayed down‐regulation of genes involved in glycolysis and lipid biosynthesis and increased expression of genes involved in OXPHOS. Accordingly, 3D cultures of hiPSC‐CMs had lower fluxes through glycolysis and fatty acid synthesis and increased TCA‐cycle activity. Importantly, we demonstrated that the 3D culture environment reproducibly improved both CM purity and metabolic maturation across different hPSC lines, thereby providing a robust strategy to derive enriched hPSC‐CMs with metabolic features closer to that of adult CMs. Abstract : This study describes a simple and efficient method to generate human pluripotent stem cell‐derived cardiomyocytes (hPSC‐CMs) with improved metabolic maturation. The strategy consists in promoting cell aggregation at the cardiac progenitor stage to increase protocol reproducibility. By using an integrated experimental and computational systems biology approach, this work compares 2D monolayers and 3D aggregate cultures and shows that the later improves hPSC‐CM commitment and enrichment, and the energetic metabolism of the generated CMs more closely resembles that of adult CMs.